CaCO3 nanoparticles and preparation method thereof

The method controls CaCO3 nanoparticle size and morphology using microemulsion technology with crystal form regulators, addressing synthesis challenges and enabling broad industrial applicability.

CN119219049APending Publication Date: 2024-12-31QINGHAI SALT LAKE IND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229955.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Current methods for synthesizing CaCO3 nanoparticles lack effective control over particle size and morphology, leading to complex and difficult-to-operate processes, limiting their industrial applicability and economic value.

Method used

A method involving the formation of Na2CO3 and Ca(OH)2 microemulsions using crystal form regulators, surfactants, and cosurfactants to control the morphology and particle size of CaCO3 nanoparticles, achieved through stirring, mixing, aging, and subsequent washing and drying processes.

Benefits of technology

The method enables the production of CaCO3 nanoparticles with controlled particle sizes ranging from 29nm to 904nm and various morphologies, suitable for industrial applications, enhancing economic value and utilization of Na2CO3 by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219049A_ABST
    Figure CN119219049A_ABST
Patent Text Reader

Abstract

The invention provides CaCO3 nanoparticles and a preparation method thereof, and the preparation method comprises the following steps: respectively adding a crystal form regulating agent, a surfactant, a cosurfactant and an organic solvent into a Na2CO3 aqueous solution and a Ca (OH) 2 aqueous solution to form a Na2CO3 microemulsion and a Ca (OH) 2 microemulsion; adding the Ca (OH) 2 micro-emulsion into the Na2CO3 micro-emulsion to form a CaCO3 nano-particle crude product, and finally treating the CaCO3 nano-particle crude product to obtain CaCO3 nano-particles; wherein the crystal form regulating agent is one or more of Span-80, glucose, polyethyleneimine and L-alanine. The CaCO3 nanoparticles obtained by the preparation method have the advantages of small particle size, uniform particle dispersion, regular morphology and the like, CaCO3 can have different types of morphologies while the particle size of the CaCO3 nanoparticles is controlled, and the method is simple, easy to operate and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic nanomaterials, and in particular to a CaCO3 nanoparticle and a preparation method thereof. Background Art

[0002] There are abundant chlorine resources in salt lakes, and "chlorine balance" is a very important issue in the process of realizing the comprehensive utilization of salt lake resources. In the preparation process of hydrazine hydrate, an intermediate for synthesizing ADC foaming agent, the chlorine resources in the salt lake can be fully utilized to build a sustainable and environmentally friendly "chlorine-sodium hypochlorite-hydrazine hydrate" process system. The equation included in the preparation process is: Cl2+4NaOH+CO(NH2)2=2N2H4·H2O+2NaCl+Na2CO3. This process method uses NaClO generated by the reaction of chlorine and NaOH as a reaction substrate to synthesize hydrazine hydrate. In this process, a large amount of Na2CO3 will be produced as a by-product, and the economic added value generated by directly recovering it is low. Therefore, it can be further utilized as a raw material for the production of nano-CaCO3, further improving the economic value of the by-product Na2CO3.

[0003] Nano-CaCO3 has the characteristics of high porosity, excellent surface effect, quantum size effect and biocompatibility, and is widely used in various industrial fields such as plastics, rubber, papermaking, ink, coating, chemical building materials, cosmetics, medicine, sealants and adhesives. The morphology and particle size of CaCO3 particles are one of the key factors that determine its performance and application. CaCO3 particles with different morphologies and particle sizes have different characteristics. At the same time, in different industries, there are different requirements for the size and morphology of nano-CaCO3. For example, cubic nano-CaCO3 has the advantages of small stacking volume, low oil absorption value, good gloss, good transparency and fluidity, and has good application in the field of paint and ink. Nano-CaCO3 with long rod-shaped structure has the advantages of high whiteness, high strength and good filling performance, and is generally used in the field of rubber and plastic. Lamellar nano-CaCO3 has the advantages of good surface coating performance, strong hiding power and easy dispersion, and also has excellent optical properties and printing properties. It has many applications in the fields of papermaking, coatings, non-woven fabrics, etc. In summary, nano-CaCO3 particles of different morphologies have excellent properties in different aspects, and can be applied to different fields to exert their different properties. Therefore, the study of nano-CaCO3 with multiple morphologies and small particle sizes is of great significance for exploring the specific applications of nano-CaCO3.

[0004] Therefore, in the process of synthesizing nano-CaCO3, the chemical composition, morphology, structure, particle size distribution and other properties of calcium carbonate can be regulated to achieve the synthesis of nano-CaCO3 with different morphologies and particle sizes, thereby realizing the application of nano-CaCO3 in different industrial fields. In addition, the crystal form of calcium carbonate is divided into three types: calcite, aragonite and vaterite. Among them, calcite is one of the trigonal crystal system and has the most stable structure. It has the advantages of large covering power, high whiteness, good purity, heat resistance, corrosion resistance, and chemical stability in the use of building materials, chemical industry, medicine and other fields.

[0005] At present, the synthesis methods of nano-CaCO3 mainly include carbonization method, complex decomposition method, sol-gel method and microemulsion method. The carbonization method is simple to operate, but it has the disadvantages of long carbonization time, poor gas-liquid mass transfer and large equipment investment. The double decomposition method has a simple reaction process, high product purity and is suitable for industrial production, but the crystal form of CaCO3 obtained by this method is difficult to control, and the production cost is high and the economic benefit is poor. The particle size distribution of the CaCO3 product of the sol-gel method is uniform, and calcium carbonate with special crystal forms can be prepared, but the preparation time is long and it is difficult to achieve large-scale industrial production. The microemulsion method is to mix two immiscible solvents and surfactants under high-speed stirring to form an oil-in-water emulsion, and obtain nanoparticles after nucleation, coalescence, agglomeration and heat treatment in microbubbles. Compared with other methods for synthesizing nano-CaCO3, the product obtained by the microemulsion method has the advantages of small particle size, uniform particle distribution, controllable particle size and shape, simple operation, and easy to achieve high-purity production, and has a very good application prospect.

[0006] Studying the process conditions for preparing CaCO3 nanoparticles with different morphologies provides a feasible technical blueprint for realizing the effective utilization of abandoned Na2CO3 resources by salt lake enterprises, optimizing and expanding the utilization of solid waste resources. However, the current research on the production of CaCO3 nanoparticles with different morphologies using Na2CO3 is not mature enough, and there are few methods for morphology control of CaCO3 nanoparticles, especially the inability to control the particle size of CaCO3 nanoparticles while making CaCO3 have different morphologies. There are also problems such as complex process and difficult operation for the preparation of CaCO3 nanoparticles. Therefore, this invention is specially proposed. Summary of the invention

[0007] The main purpose of the present invention is to provide a CaCO3 nanoparticle and a preparation method thereof, so as to solve the problems in the prior art that there are few methods for controlling the morphology of CaCO3 nanoparticles, it is impossible to control the particle size of CaCO3 nanoparticles while making the CaCO3 nanoparticles have different morphologies, and the preparation process of CaCO3 nanoparticles is complicated and difficult to operate.

[0008] In order to solve the above problems, the present application provides a method for preparing CaCO3 nanoparticles, which comprises the following steps: step (1), adding a first crystal form regulator, a first surfactant, a first cosurfactant and a first organic solvent to a Na2CO3 aqueous solution, stirring and mixing to form a Na2CO3 microemulsion; step (2), adding a second crystal form regulator, a second surfactant, a second cosurfactant and a second organic solvent to a Ca(OH)2 aqueous solution, stirring and mixing to form a Ca(OH)2 microemulsion; step (3), adding the Ca(OH)2 microemulsion to the Na2CO3 microemulsion, stirring and aging to form a crude CaCO3 nanoparticle; step (4), washing, precipitating and drying the crude CaCO3 nanoparticle to obtain CaCO3 nanoparticles; wherein the crystal form regulator is one or more of Span-80, glucose, polyethyleneimine and L-alanine.

[0009] Furthermore, the crystal form regulator is at least two of Span-80, glucose, polyethyleneimine and L-alanine; preferably, the crystal form regulator is a compound of polyethyleneimine and L-alanine in a mass ratio of (1-2):1; or, the crystal form regulator is a compound of polyethyleneimine and Span-80 in a mass ratio of 1:(80-120); preferably, the amount of the first crystal form regulator added in step (1) is 9% to 12% of the weight of Na2CO3 in the Na2CO3 aqueous solution; preferably, the amount of the second crystal form regulator added in step (2) is 12% to 15% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution.

[0010] Furthermore, the concentration of Na2CO3 in the Na2CO3 microemulsion is 0.25 to 1.2 mol / L, and the concentration of Ca(OH)2 in the Ca(OH)2 microemulsion is 0.25 to 1.2 mol / L.

[0011] Further, the first surfactant and the second surfactant are independently selected from hexadecyltrimethylammonium bromide and / or Span-80; preferably, the first co-surfactant and the second co-surfactant are independently selected from n-butanol and / or n-pentanol; preferably, the first organic solvent and the second organic solvent are independently selected from cyclohexane and / or isooctane.

[0012] Furthermore, in step (1), the amount of the first surfactant added is 2% to 5% of the weight of Na2CO3 in the Na2CO3 aqueous solution; preferably, the amount of the first co-surfactant added is 7% to 10% of the weight of Na2CO3 in the Na2CO3 aqueous solution; preferably, the amount of the first organic solvent added is 35% to 38% of the weight of Na2CO3 in the Na2CO3 aqueous solution.

[0013] Furthermore, in step (2), the amount of the second surfactant added is 6% to 8% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution; preferably, the amount of the second co-surfactant added is 10% to 12% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution; preferably, the amount of the second organic solvent added is 50% to 55% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution.

[0014] Furthermore, in step (3), the molar ratio of Ca(OH)2 in the Ca(OH)2 microemulsion and Na2CO3 in the Na2CO3 microemulsion is (0.5-2):1.

[0015] Furthermore, in step (3), the Ca(OH)2 microemulsion is added to the Na2CO3 microemulsion via a peristaltic pump; preferably, the rotation speed of the peristaltic pump is 50 to 100 rpm; preferably, the stirring time is 1 to 3 hours; preferably, the aging time is 10 to 15 hours.

[0016] Furthermore, in step (4), the washing detergent is water and / or anhydrous ethanol; preferably, the drying time is 10 to 15 hours; preferably, the drying temperature is 60 to 100°C.

[0017] According to another aspect of the present invention, a CaCO3 nanoparticle is provided, which is prepared by the above-mentioned preparation method, and the average particle size of the CaCO3 nanoparticle is in the range of 29nm to 904nm, and the structure of the CaCO3 nanoparticle is a cubic structure, a hollow long rod structure, a blocky cubic structure, a regular tetrahedron structure, a hollow cubic structure or a lamellar cubic structure.

[0018] The present invention provides a method for preparing CaCO3 nanoparticles. By applying the technical scheme of the present invention, the following technical objectives can be achieved: (1) The method for preparing calcium carbonate nanomaterials provided by the present invention prepares stable Na2CO3 and Ca(OH)2 oil-in-water microemulsions. By controlling the reaction conditions and mixing the two microemulsions, the average particle size of the CaCO3 nanoparticles can be controlled within the range of 29nm to 904nm, both within the nanometer range; (2) By adding one or more crystal form regulators selected from Span-80, glucose, polyethyleneimine and L-alanine, the CaCO3 nanoparticles can have different types of morphologies, thereby achieving the purpose of controlling the particle size of the CaCO3 nanoparticles while enabling the CaCO3 to have different types of morphologies. The obtained CaCO3 nanoparticles have multiple advantages such as small particle size, uniform particle dispersion, regular morphology and the like; (3) The method for preparing CaCO3 nanoparticles provided by the present invention has a simple preparation process, is easy to operate, does not require conditions such as high temperature and high pressure, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0020] Figure 1 Schematic diagram of the mechanism of preparing CaCO3 nanoparticles by the microemulsion method of the present invention;

[0021] Figure 2 This is the X-ray diffraction pattern of the CaCO3 nanoparticles prepared in Example 1;

[0022] Figure 3 This is a SEM image of the CaCO3 nanoparticles prepared in Example 1;

[0023] Figure 4 This is a SEM image of the CaCO3 nanoparticles prepared in Example 14;

[0024] Figure 5 This is a SEM image of the CaCO3 nanoparticles prepared in Example 15;

[0025] Figure 6 This is a SEM image of the CaCO3 nanoparticles prepared in Example 16;

[0026] Figure 7 This is a SEM image of the CaCO3 nanoparticles prepared in Example 17;

[0027] Figure 8 This is a SEM image of the CaCO3 nanoparticles prepared in Example 19;

[0028] Fig. 9 This is a SEM image of the CaCO3 nanoparticles prepared in Example 21;

[0029] Fig.10 This is the SEM image of the CaCO3 nanoparticles prepared in Comparative Example 1. DETAILED DESCRIPTION

[0030] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0031] As described in the background technology part, in the process of utilizing salt lake resources to prepare hydrazine hydrate, a large amount of Na2CO3 by-products can be produced, in order to improve the economic added value of by-product, it is further utilized to make it as the raw material of producing nano-CaCO3. The CaCO3 nano-particles of different morphologies often have different properties, and the requirements of the required nano-CaCO3 for particle diameter, morphology, etc. are also different according to the different industry field demands. At present, for the preparation of nano-CaCO3 particles, there are still many problems, for example: the CaCO3 nano-particle morphology is not abundant enough, and the morphology control method of CaCO3 nano-particles is also less, and it is not possible to control the CaCO3 nano-particles particle diameter while also controlling its morphology, and the CaCO3 nano-particles preparation process is complicated, difficult to operate, etc.

[0032] In order to solve the above problems, the present invention provides a method for preparing CaCO3 nanoparticles, which comprises the following steps: step (1), adding a first crystal form regulator, a first surfactant, a first cosurfactant and a first organic solvent to a Na2CO3 aqueous solution, stirring and mixing to form a Na2CO3 microemulsion; step (2), adding a second crystal form regulator, a second surfactant, a second cosurfactant and a second organic solvent to a Ca(OH)2 aqueous solution, stirring and mixing to form a Ca(OH)2 microemulsion; step (3), adding the Ca(OH)2 microemulsion to the Na2CO3 microemulsion, stirring and aging to form a crude CaCO3 nanoparticle; step (4), washing, precipitating and drying the crude CaCO3 nanoparticle to obtain CaCO3 nanoparticles; wherein the crystal form regulator is one or more of Span-80, glucose, polyethyleneimine and L-alanine.

[0033] The method firstly stirs and mixes a first crystal form regulator, a first surfactant, a first co-surfactant and a first organic solvent to form a Na2CO3 microemulsion; then stirs and mixes a second crystal form regulator, a second surfactant, a second co-surfactant and a second organic solvent to form a Ca(OH)2 microemulsion; then adds the Ca(OH)2 microemulsion to the Na2CO3 microemulsion, and obtains CaCO3 nanoparticles through a series of operations including stirring, aging, washing, precipitation and drying.

[0034] Specifically, the present application uses a Na2CO3 microemulsion made of a Na2CO3 aqueous solution and a Ca(OH)2 microemulsion made of a Ca(OH)2 aqueous solution, and the two microemulsions are mixed to react to prepare CaCO3 nanoparticles. The reaction equation included in the method for preparing CaCO3 nanoparticles is Na2CO3+Ca(OH)2=2NaOH+CaCO3. Na2CO3 is a by-product produced in the process of utilizing salt lake resources. The method for preparing CaCO3 nanoparticles using Na2CO3 can effectively make comprehensive use of the by-product Na2CO3. In particular, in the process of preparing nano-CaCO3 particles, another raw material selected for the reaction is Ca(OH)2. On the one hand, because Ca(OH)2 is an alkali with a slightly soluble property, its slightly soluble property can be utilized to make the formed microemulsion more uniform when preparing the Ca(OH)2 microemulsion, and then it can react better with the Na2CO3 microemulsion, so as to form CaCO3 nanoparticles with smaller particle size and more uniformity, and it will also have a certain positive impact on the morphology of the CaCO3 nanoparticles. On the other hand, selecting Ca(OH)2 as a reaction raw material to react with Na2CO3 to prepare CaCO3 nanoparticles can produce NaOH during the reaction. As described in the background technology section, the reaction equation included in the process of preparing hydrazine hydrate using the "chlorine-sodium hypochlorite-hydrazine hydrate" process system is: Cl2+4NaOH+CO(NH2)2=2N2H4·H2O+2NaCl+Na2CO3, and the preparation process will produce a large amount of Na2CO3 as a by-product. NaOH is also used in this preparation process. Therefore, selecting Ca(OH)2 and Na2CO3 as reaction raw materials to prepare CaCO3 nanoparticles can not only improve the economic added value of the by-product Na2CO3, but also recycle the generated NaOH to the synthesis process of hydrazine hydrate, further improving the utilization rate of NaOH, having environmentally friendly characteristics, and reducing production costs. In addition, the microemulsion method is selected to prepare CaCO3 nanoparticles, without the operation of high-temperature heating, the method is simple and easy to control, not limited by equipment, and is more applicable in industrial production processes.

[0035] In particular, the same or different types of crystal form regulators are added in the process of preparing Na2CO3 microemulsion and Ca(OH)2 microemulsion. The added crystal form regulator is one or more of Span-80, glucose, polyethyleneimine and L-alanine. Span-80 is a non-ionic surfactant. The hydrophilic part (sorbitan) and the hydrophobic part (oleate) in the molecular structure give it the characteristics of a surfactant. At the same time, it can form a stable emulsion at the oil-water interface. These characteristics also enable it to play a role in regulating the direction of molecular growth and regulating molecular morphology. Glucose is a kind of sugar crystal form regulator, polyethyleneimine is a cationic polymer crystal form regulator rich in amine groups, and L-alanine is one of the amino acid crystal form regulators. In the process of preparing CaCO3 nanoparticles, by adding the above-mentioned crystal form regulators, the purpose of regulating the growth morphology of CaCO3 nanoparticles can be achieved. The present invention uses a microemulsion method to prepare Na2CO3 microemulsion and Ca(OH)2 microemulsion, and respectively adds a crystal form regulator to influence the growth of CaCO3 nanoparticles, thereby achieving the purpose of the morphology of the CaCO3 nanoparticles. In addition, when the crystal form regulator is added during the preparation of the CaCO3 nanoparticles, the crystal form regulator can be coated on the surface of the calcium carbonate, thereby preventing the solvent from preferentially forming a coating on the surface, forming a protective layer on the surface of the calcium carbonate through physical adsorption and chemical adsorption, avoiding the agglomeration and agglomeration of the formed calcium carbonate particles, improving the dispersion performance thereof, and facilitating the formation of more uniform CaCO3 nanoparticles.

[0036] Moreover, the present invention has found through a large number of studies that the use of a variety of these different types of crystal form regulators can guide the CaCO3 nanoparticles to change the crystal form produced when using a single crystal form regulator during the growth process, thereby forming more types of CaCO3 nanoparticle morphology. This may be because: the crystal form controller is often adsorbed on the crystal surface of the microcrystal, by changing the intermolecular interface properties during the growth process, changing the original chemical balance, changing the characteristics of various aspects such as the nucleation rate of each crystal face, so that the CaCO3 nanoparticles grow in a specific direction guided by a variety of crystal form regulators, and finally reach the purpose of further regulating the direction of crystal growth. The use of a variety of mixed crystal form regulators enriches the control method of the CaCO3 nanoparticle morphology, especially, the mixed compound use of these different types of crystal form regulators can obtain CaCO3 nanoparticles of different morphologies, and can also make the morphology of the obtained CaCO3 nanoparticles more regular, and the dispersion and particle size uniformity can also play a significant improvement role.

[0037] In order to better achieve the purpose of regulating the morphology of CaCO3 nanoparticles, in a preferred embodiment, the crystal form regulator is at least two of Span-80, glucose, polyethyleneimine and L-alanine. Different types of crystal form regulators have different effects on the intermolecular interface properties, chemical equilibrium, nucleation rate of each crystal face, etc. in the process of guiding the growth of CaCO3 nanoparticles. Selecting at least two different types of crystal form regulators for compounding can jointly affect the growth of CaCO3 nanoparticles, thereby achieving the purpose of further regulating the morphology of CaCO3 nanoparticles. In particular, we found that the CaCO3 nanoparticles obtained using the compounded crystal form regulator have the advantages of better uniformity of dispersion and particle size and more regular morphology. In order to give full play to the above-mentioned regulatory effect, preferably, the crystal form regulator is a compound of polyethyleneimine and L-alanine in a mass ratio of (1 to 2): 1; or, the crystal form regulator is a compound of polyethyleneimine and Span-80 in a mass ratio of 1: (80 to 120). The crystal form regulator is compounded in this ratio, and the obtained CaCO3 nanoparticles not only have a regular and single morphology, but also have a better uniformity of particle size. More preferably, the amount of the first crystal form regulator added in step (1) is 9% to 12% of the weight of Na2CO3 in the Na2CO3 aqueous solution; preferably, the amount of the second crystal form regulator added in step (2) is 12% to 15% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution. When the amount of the crystal form regulator added is within this range, the purpose of better regulating the crystal form can be achieved. In particular, when adding the crystal form regulator, it is dissolved in water in advance and then added for better results.

[0038] In a preferred embodiment, the concentration of Na2CO3 in the Na2CO3 microemulsion is 0.25-1.2 mol / L, and the concentration of Ca(OH)2 in the Ca(OH)2 microemulsion is 0.25-1.2 mol / L. In the process of preparing CaCO3 nanoparticles by microemulsion method, the concentration of the microemulsion prepared by the reaction raw materials Na2CO3 and Ca(OH)2 will have a great influence on the particle size and uniformity of the CaCO3 nanoparticles. After a series of exploratory experiments, in the method for preparing CaCO3 nanoparticles provided by the present invention, the concentration of Na2CO3 in the Na2CO3 microemulsion and the concentration of Ca(OH)2 in the Ca(OH)2 microemulsion are respectively controlled within this range, so that the reaction of the two microemulsions can better control the particle size of the CaCO3 nanoparticles within a nanometer range, and also make its uniformity and dispersibility better.

[0039] In a preferred embodiment, the first surfactant and the second surfactant are independently selected from hexadecyltrimethylammonium bromide (CTAB) and / or Span-80; preferably, the first co-surfactant and the second co-surfactant are independently selected from n-butanol and / or n-pentanol; preferably, the first organic solvent and the second organic solvent are independently selected from cyclohexane and / or isooctane. In the process of preparing two microemulsions respectively, adding a surfactant can improve the dispersion and affinity of the microemulsion, and adding a co-surfactant and an organic solvent will obtain more stable Na2CO3 and Ca(OH)2 oil-in-water microemulsions, which is more conducive to regulating the particle size and morphology of CaCO3 nanoparticles. In the process of preparing Na2CO3 microemulsions and Ca(OH)2 microemulsions, the above-mentioned surfactants, co-surfactants and organic solvents are used independently to achieve the purpose of better controlling the particle size and morphology of CaCO3 nanoparticles. In particular, when adding a surfactant, dissolving it in water in advance and then adding it can obtain better results.

[0040] In a preferred embodiment, the amount of the first surfactant added in step (1) is 2% to 5% of the weight of Na2CO3 in the Na2CO3 aqueous solution; preferably, the amount of the first co-surfactant added is 7% to 10% of the weight of Na2CO3 in the Na2CO3 aqueous solution; preferably, the amount of the first organic solvent added is 35% to 38% of the weight of Na2CO3 in the Na2CO3 aqueous solution. In the process of preparing the Na2CO3 microemulsion, controlling the amount of the above components within the above range can produce a better effect on controlling the particle size and morphology of the CaCO3 nanoparticles.

[0041] Furthermore, in a preferred embodiment, the amount of the second surfactant added in step (2) is 6% to 8% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution; preferably, the amount of the second co-surfactant added is 10% to 12% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution; preferably, the amount of the second organic solvent added is 50% to 55% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution. In the process of preparing the Ca(OH)2 microemulsion, controlling the usage of the above three components within the above range can produce a further beneficial effect on controlling the particle size and morphology of the Ca(OH)2 nanoparticles.

[0042] In a preferred embodiment, in step (3), the molar ratio of Ca(OH)2 in the Ca(OH)2 microemulsion and Na2CO3 in the Na2CO3 microemulsion is (0.5-2):1. In the process of preparing CaCO3 nanoparticles by microemulsion method, the ratio of the two raw materials will affect the formation of CaCO3 nanoparticles. In particular, the present invention adopts the reaction of Na2CO3 microemulsion and Ca(OH)2 microemulsion, which involves the reaction of Na2CO3 and Ca(OH)2. Controlling the molar ratio of the two raw materials will have an impact on the yield, morphology, particle size and other aspects of the CaCO3 nanoparticles. Controlling the addition ratio of the two microemulsions within the above range can achieve a better control effect on the particle size and morphology of the CaCO3 nanoparticles.

[0043] In a preferred embodiment, in step (3), the Ca(OH)2 microemulsion is added to the Na2CO3 microemulsion by a peristaltic pump; the speed of adding the Ca(OH)2 microemulsion to the Na2CO3 microemulsion is controlled to obtain better CaCO3 nanoparticles. Preferably, the rotation speed of the peristaltic pump is 50 to 100 rpm; preferably, the stirring time is 1 to 3 hours; preferably, the aging time is 10 to 15 hours. Controlling the specific parameters of the above-mentioned operation steps within this range will make the obtained CaCO3 nanoparticles have better properties such as particle size and morphology.

[0044] In a preferred embodiment, in step (4), the washing detergent is water and / or anhydrous ethanol; preferably, the drying time is 10 to 15 hours; preferably, the drying temperature is 60 to 100° C. The washing operation and the drying operation are both for making the obtained CaCO3 nanoparticles have better purity and state. By controlling the washing detergent to be water and / or anhydrous ethanol and controlling the drying time and the drying temperature to be within the above range, CaCO3 nanoparticles with higher purity and state can be obtained.

[0045] According to another aspect of the present invention, a kind of CaCO3 nanoparticle is also provided, and this CaCO3 nanoparticle is prepared by the above-mentioned preparation method, and the average particle size of the CaCO3 nanoparticle can be controlled within the range of 29nm to 904nm, and the obtained CaCO3 nanoparticle has a cubic structure, a hollow long rod-shaped structure, a blocky cubic structure, a regular tetrahedron structure, a hollow cubic structure and a lamellar cubic structure. In actual application, according to the difference in morphology and particle size of the obtained CaCO3 nanoparticle, the obtained CaCO3 nanoparticle can be applied to different fields, and has a very broad application prospect.

[0046] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0047] In order to more clearly describe the scheme described in the present application, it should be noted that the percentage of the amount of each component added when preparing the two microemulsions of Ca(OH)2 and Na2CO3 in the embodiments and comparative examples is based on the weight of the added Ca(OH)2 or Na2CO3; the percentage of the amount of each component added when preparing the CaCl2 microemulsion in Comparative Example 2 is based on the weight of the added CaCl2.

[0048] Example 1

[0049] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0050] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 6.8% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0051] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0052] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. X-ray diffraction test and scanning electron microscope SEM test were also performed on them. The X-ray diffraction pattern is shown in Table 1. Figure 2 As shown, its SEM image is as follows Figure 3 As shown, in addition, Figure 1 Schematic diagram of the mechanism of preparing CaCO3 nanoparticles by the microemulsion method of the present invention.

[0053] Example 2

[0054] The difference from Example 1 is that the concentration of Na2CO3 is 0.25 mol / L and the concentration of Ca(OH)2 is 0.25 mol / L.

[0055] Na2CO3 and water were mixed evenly, 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 0.25 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0056] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 6.8% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 0.25 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0057] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0058] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0059] Example 3

[0060] The difference from Example 1 is that the concentration of CaCO3 is 1.2 mol / L and the concentration of Ca(OH)2 is 1.2 mol / L.

[0061] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1.2 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0062] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 6.8% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1.2 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0063] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0064] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0065] Example 4

[0066] The difference from Example 1 is that the concentration of CaCO3 is 2 mol / L and the concentration of Ca(OH)2 is 2 mol / L.

[0067] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 2 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0068] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 6.8% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 2 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0069] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0070] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0071] Example 5

[0072] The difference from Example 1 is that the amount of the first surfactant CTAB added is 2%, and the amount of the second surfactant CTAB added is 6%.

[0073] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 2% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0074] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 6% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0075] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0076] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0077] Example 6

[0078] The difference from Example 1 is that the amount of the first surfactant CTAB added is 5%, and the amount of the second surfactant CTAB added is 8%.

[0079] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 5% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0080] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 8% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0081] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0082] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0083] Example 7

[0084] The difference from Example 1 is that the amount of the first surfactant CTAB added is 10%, and the amount of the second surfactant CTAB added is 10%.

[0085] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 10% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0086] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 10% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0087] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0088] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0089] Example 8

[0090] The difference from Example 1 is that the amount of the first organic solvent added is 35%, and the amount of the second organic solvent added is 50%.

[0091] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 35% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0092] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 8% CTAB, 11% n-butanol and 50% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0093] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0094] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0095] Example 9

[0096] The difference from Example 1 is that the amount of the first organic solvent added is 38%, and the amount of the second organic solvent added is 55%.

[0097] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 38% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0098] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 8% CTAB, 11% n-butanol and 55% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0099] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0100] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0101] Example 10

[0102] The difference from Example 1 is that the amount of the first organic solvent added is 45%, and the amount of the second organic solvent added is 65%.

[0103] Na2CO3 and water were uniformly mixed, 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 45% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0104] Ca(OH)2 and water were mixed evenly, 13.5% Span-80, 8% CTAB, 11% n-butanol and 65% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0105] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0106] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0107] Embodiment 11

[0108] The difference from Example 1 is that the amount of the first crystal form regulator is controlled to be 20% of the weight of Na2CO3 in the Na2CO3 aqueous solution, the amount of the first surfactant is controlled to be 20% of the weight of Na2CO3 in the Na2CO3 aqueous solution; the amount of the first cosurfactant is 15% of the weight of Na2CO3 in the Na2CO3 aqueous solution; and the amount of the first organic solvent is 50% of the weight of Na2CO3 in the Na2CO3 aqueous solution. The amount of the first crystal form regulator is controlled to be 20% of the weight of Na2CO3 in the Na2CO3 aqueous solution, the amount of the first surfactant is controlled to be 15% of the weight of Ca(OH)2 in the aqueous solution; the amount of the first cosurfactant is 30% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution; and the amount of the first organic solvent is 70% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution.

[0109] Na2CO3 and water were mixed evenly, and 20% Span-80, 20% CTAB, 15% n-butanol and 50% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0110] Ca(OH)2 and water were mixed evenly, and 20% Span-80, 15% CTAB, 30% n-butanol and 70% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0111] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0112] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0113] Example 12

[0114] Na2CO3 and water were mixed evenly, and 9% Span-80, 4.5% CTAB, 7% n-pentanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0115] Ca(OH)2 and water were mixed evenly, and 15% Span-80, 6.8% CTAB, 10% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0116] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 2:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 50 rpm, stirred for 1 hour and aged for 10 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 60°C for 15 hours to obtain CaCO3 nanoparticles.

[0117] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0118] Embodiment 13

[0119] Na2CO3 and water were mixed evenly, 12% Span-80 as a crystal form regulator, 4.5% Span-80 as a surfactant, 10% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 was dissolved in water before being added as a surfactant.

[0120] Ca(OH)2 and water were mixed evenly, 12% Span-80 as a crystal form regulator, 6.8% Span-80 (as a surfactant), 12% n-butanol and 53% isooctane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Span-80 was dissolved in water before being added as a surfactant.

[0121] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 0.5:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 100 rpm, stirred for 3 hours and aged for 15 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 100°C for 10 hours to obtain CaCO3 nanoparticles.

[0122] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0123] Embodiment 14

[0124] The crystal form regulator in Example 1 was changed to glucose.

[0125] Na2CO3 and water were uniformly mixed, 10% glucose, 4.5% CTAB, 7% n-butanol and 37% cyclohexane were added thereto, and the mixture was stirred for 30 minutes to obtain a Na2CO3 microemulsion having a Na2CO3 content of 1 mol / L. Glucose and CTAB were respectively dissolved in water before being added.

[0126] Ca(OH)2 and water were mixed evenly, 13% glucose, 6.8% CTAB, 10% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Glucose and CTAB were respectively dissolved in water before being added.

[0127] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0128] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. The results of the SEM test are shown in Table 1. Figure 4 shown.

[0129] Embodiment 15

[0130] The crystal form regulator in Example 1 was changed to polyethyleneimine.

[0131] Na2CO3 and water were mixed evenly, and 10% polyethyleneimine, 4.5% CTAB, 7% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Wherein, when adding polyethyleneimine and CTAB, they were respectively dissolved in water in advance.

[0132] Ca(OH)2 and water were mixed evenly, and 13% polyethyleneimine, 6.8% CTAB, 10% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Wherein, when adding polyethyleneimine and CTAB, they were respectively dissolved in water in advance.

[0133] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0134] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. The results of the SEM test are shown in Table 1. Figure 5 shown.

[0135] Example 16

[0136] The crystal form regulator in Example 1 was changed to L-alanine.

[0137] Na2CO3 and water were mixed evenly, 10% L-alanine, 4.5% CTAB, 7% n-butanol and 37% cyclohexane were added thereto, and the mixture was stirred for 30 minutes to obtain a Na2CO3 microemulsion having a Na2CO3 content of 1 mol / L. L-alanine and CTAB were respectively dissolved in water before being added.

[0138] Ca(OH)2 and water were mixed evenly, 13% L-alanine, 6.8% CTAB, 10% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. L-alanine and CTAB were respectively dissolved in water before being added.

[0139] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0140] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. The results of the SEM test are shown in Table 1. Figure 6 shown.

[0141] Embodiment 17

[0142] The crystal form regulator in Example 1 is changed to polyethyleneimine and L-alanine, and the two are compounded in a mass ratio of 1:1.

[0143] Na2CO3 and water were mixed evenly, and 10% of a mixture of polyethyleneimine and L-alanine, 4.5% of CTAB, 7% of n-butanol and 37% of cyclohexane were added thereto, and the mixture was stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. The mixture of polyethyleneimine and L-alanine and CTAB were dissolved in water before adding them, and polyethyleneimine and L-alanine were compounded at a mass ratio of 1:1.

[0144] Ca(OH)2 and water were mixed evenly, and 13% of a mixture of polyethyleneimine and L-alanine, 6.8% of CTAB, 10% of n-butanol and 53% of cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. The polyethyleneimine and L-alanine mixture and CTAB were respectively dissolved in water before being added, and the polyethyleneimine and L-alanine were compounded in a mass ratio of 1:1.

[0145] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0146] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. The results of the SEM test are shown in Table 1. Figure 7 shown.

[0147] Embodiment 18

[0148] The crystal form regulator in Example 1 is changed to polyethyleneimine and L-alanine, and the two are compounded in a mass ratio of 2:1.

[0149] Na2CO3 and water were mixed evenly, and 10% of a mixture of polyethyleneimine and L-alanine, 4.5% of CTAB, 7% of n-butanol and 37% of cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Wherein, polyethyleneimine, L-alanine and CTAB were respectively dissolved in water before being added, and polyethyleneimine and L-alanine were compounded at a mass ratio of 2:1.

[0150] Ca(OH)2 and water were mixed evenly, and 13% of a mixture of polyethyleneimine and L-alanine, 6.8% of CTAB, 10% of n-butanol and 53% of cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Wherein, polyethyleneimine, L-alanine and CTAB were respectively dissolved in water before adding them, and polyethyleneimine and L-alanine were compounded at a mass ratio of 2:1.

[0151] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0152] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0153] Embodiment 19

[0154] The crystal form regulator in Example 1 is changed to polyethyleneimine and Span-80, and the two are compounded in a mass ratio of 1:80.

[0155] Na2CO3 and water were mixed evenly, 10% of Span-80 and polyethyleneimine mixture, 4.5% of CTAB, 7% of n-butanol and 37% of cyclohexane were added thereto, and the mixture was stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. The Span-80 and polyethyleneimine mixture and CTAB were respectively dissolved in water before being added, and the polyethyleneimine and Span-80 mixture were compounded at a mass ratio of 1:80.

[0156] Ca(OH)2 and water were mixed evenly, and 13% of Span-80 and polyethyleneimine mixture, 6.8% of CTAB, 10% of n-butanol and 53% of cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Among them, when adding the Span-80 and polyethyleneimine mixture and CTAB, they were pre-dissolved in water, and the polyethyleneimine and Span-80 mixture were compounded at a mass ratio of 1:80.

[0157] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0158] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. The results of the SEM test are shown in Table 1. Figure 8 shown.

[0159] Embodiment 20

[0160] The crystal form regulator in Example 1 was changed to polyethyleneimine and Span-80, and the mass ratio of the two was 1:120.

[0161] Na2CO3 and water were mixed evenly, 10% of Span-80 and polyethyleneimine mixture, 4.5% of CTAB, 7% of n-butanol and 37% of cyclohexane were added thereto, and the mixture was stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. The Span-80 and polyethyleneimine mixture and CTAB were respectively dissolved in water before being added, and the polyethyleneimine and Span-80 mixture were compounded at a mass ratio of 1:120.

[0162] Ca(OH)2 and water were mixed evenly, and 13% of Span-80 and polyethyleneimine mixture, 6.8% of CTAB, 10% of n-butanol and 53% of cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Among them, when adding the Span-80 and polyethyleneimine mixture and CTAB, they were pre-dissolved in water, and the polyethyleneimine and Span-80 mixture were compounded at a mass ratio of 1:120.

[0163] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0164] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0165] Embodiment 21

[0166] The crystal form regulator in Example 1 was changed to Span-80 and L-alanine, and the two were compounded in a mass ratio of 100:1.

[0167] Na2CO3 and water were mixed evenly, and 9.5% of a mixture of Span-80 and L-alanine, 4.5% of CTAB, 7% of n-butanol and 37% of cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. The mixture of Span-80 and L-alanine and CTAB were respectively dissolved in water in advance, and Span-80 and L-alanine were compounded at a mass ratio of 100:1.

[0168] Ca(OH)2 and water were mixed evenly, and 13.6% of a mixture of Span-80 and L-alanine, 6.8% of CTAB, 10% of n-butanol and 53% of cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L. Among them, the mixture of Span-80 and L-alanine and CTAB were pre-dissolved in water, respectively, and Span-80 and L-alanine were compounded at a mass ratio of 100:1.

[0169] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and Ca(OH)2 in Ca(OH)2 microemulsion of 1:1, the Ca(OH)2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0170] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. The results of the SEM test are shown in Table 1. Fig. 9 shown.

[0171] Comparative Example 1

[0172] The CaCO3 nanoparticles were prepared by conventional double decomposition method.

[0173] Using Na2CO3 and Ca(OH)2 as raw materials, according to the molar ratio of Na2CO3 to Ca(OH)2 of 1:1, Ca(OH)2 was added to the Na2CO3 solution through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0174] The CaCO3 nanoparticles were tested and recorded for their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties. The results are shown in Table 1. The results of the SEM test are shown in Table 1. Fig.10 shown.

[0175] Comparative Example 2

[0176] The difference from Example 1 is that the raw materials Na2CO3 and Ca(OH)2 are replaced by Na2CO3 and CaCl2.

[0177] Na2CO3 and water were mixed evenly, and 9.4% Span-80, 4.5% CTAB, 7.6% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0178] CaCl2 and water were uniformly mixed, 13.5% Span-80, 6.8% CTAB, 11% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a CaCl2 microemulsion with a CaCl2 content of 1 mol / L. Span-80 and CTAB were respectively dissolved in water before being added.

[0179] According to the molar ratio of Na2CO3 in Na2CO3 microemulsion and CaCl2 in CaCl2 microemulsion of 1:1, the CaCl2 microemulsion was added to the Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0180] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0181] Comparative Example 3

[0182] The difference from Example 1 is that no crystal form regulator is added.

[0183] Na2CO3 and water were mixed evenly, 4.5% CTAB, 7% n-butanol and 37% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Na2CO3 microemulsion with a Na2CO3 content of 1 mol / L, wherein CTAB was dissolved in water in advance.

[0184] Ca(OH)2 and water were mixed evenly, 6.8% CTAB, 10% n-butanol and 53% cyclohexane were added thereto, and stirred for 30 minutes to obtain a Ca(OH)2 microemulsion with a Ca(OH)2 content of 1 mol / L, wherein CTAB was dissolved in water in advance.

[0185] According to the molar ratio of Na2CO3 microemulsion to Ca(OH)2 microemulsion of 1:1, Ca(OH)2 microemulsion was added to Na2CO3 microemulsion through a peristaltic pump at a speed of 60 rpm, stirred for 2 hours and aged for 12 hours to obtain the product CaCO3 nanoparticles crude product; finally, the CaCO3 nanoparticles crude product was washed with anhydrous ethanol and dried at 80°C for 12 hours to obtain CaCO3 nanoparticles.

[0186] The CaCO3 nanoparticles were taken and their purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties were tested and recorded. The results are shown in Table 1.

[0187] The purity, morphology, whiteness, average particle size, specific surface area, particle size distribution index and other properties of the CaCO3 nanoparticles obtained in Examples 1 to 21 and Comparative Examples 1 to 3 were tested and recorded. The results are shown in Table 1.

[0188] Table 1

[0189]

[0190]

[0191] In Examples 1 to 13, when the CaCO3 nanoparticles were prepared by the microemulsion method, the amount of each component added and the experimental parameters were explored on the basis of the added crystal form regulator Span-80. The results in the analysis table show that by controlling the amount of each component added within a suitable range, the purity of the obtained CaCO3 nanoparticles can be maintained at more than 98%, the morphological characteristics of the CaCO3 nanoparticles are more regular, the particle size of the CaCO3 nanoparticles can also be controlled within a lower range, and the obtained CaCO3 nanoparticles can also have a better specific surface area. In addition, the CaCO3 nanoparticles prepared in Example 1 were subjected to an X-ray diffraction test, and the test results showed that the obtained CaCO3 nanoparticles were calcite crystals, and the CaCO3 nanoparticles of this type of crystal structure had more stable characteristics.

[0192] In Example 14 to Example 21, when preparing CaCO3 nanoparticles by microemulsion method, different types of crystal form regulators are added and the crystal form regulators are compounded to obtain CaCO3 nanoparticles with different morphological properties. These morphologies include hollow long rod-like structures, blocky cubic structures, regular tetrahedral structures, hollow cubic structures, and lamellar cubic structures, etc., which greatly enrich the morphology of CaCO3 nanoparticles. Among them, Example 17 to Example 21 uses the crystal form regulator to prepare CaCO3 nanoparticles, and the average particle size of the obtained CaCO3 nanoparticles can be controlled at a minimum of 207nm, and the maximum average particle size is also 904nm. In addition, when the crystal form regulator is compounded, the morphology of the CaCO3 nanoparticles within the preferred range is more regular and single, and the average particle size is also smaller, which has good application prospects.

[0193] Comparative Example 1 is prepared by conventional double decomposition method, and the obtained CaCO3 nanoparticles present irregular morphology, poor dispersion, and poor particle size and uniformity. The difference between Comparative Example 2 and Example 1 is that only one of the raw materials, Ca(OH)2, is replaced with CaCl2. Comparing the test results of the two methods, the particle size of the CaCO3 nanoparticles prepared by the microemulsion method using Ca(OH)2 as raw material in this application is smaller, the specific surface area is larger, and Comparative Example 2 cannot achieve the purpose of recovering NaOH alkali in practical applications, from which it can be concluded that the use of Ca(OH)2 described in the present invention as raw material to prepare CaCO3 nanoparticles is better. The difference between Comparative Example 3 and Example 1 is that no crystal form regulator is added, and the obtained CaCO3 nanoparticles have irregular morphology, which is far from the effect in the embodiment of the present invention.

[0194] In summary, the present application uses a microemulsion method to prepare CaCO3 nanoparticles, and by adding a crystal form regulator, the obtained CaCO3 nanoparticles have different types of morphologies. The obtained CaCO3 nanoparticles have multiple advantages such as small particle size, uniform particle dispersion, and more regular morphological structure, achieving the purpose of controlling the particle size of CaCO3 nanoparticles while also enabling CaCO3 to have different types of morphologies. In addition, the preparation method of CaCO3 nanoparticles provided by the present application has a simple preparation process, is easy to operate, and does not require conditions such as high temperature and high pressure, and is suitable for industrial production.

[0195] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing CaCO3 nanoparticles, characterized in that: The preparation method comprises the following steps: Step (1), adding a first crystal form regulator, a first surfactant, a first co-surfactant and a first organic solvent to a Na2CO3 aqueous solution, stirring and mixing, to form a Na2CO3 microemulsion; Step (2), adding a second crystal form regulator, a second surfactant, a second co-surfactant and a second organic solvent to the Ca(OH)2 aqueous solution, stirring and mixing to form a Ca(OH)2 microemulsion; Step (3), adding the Ca(OH)2 microemulsion to the Na2CO3 microemulsion, stirring and aging to form crude CaCO3 nanoparticles; Step (4), washing, precipitating and drying the crude CaCO3 nanoparticles to obtain the CaCO3 nanoparticles; Wherein, the crystal form regulator is one or more of Span-80, glucose, polyethyleneimine and L-alanine.

2. The method for preparing CaCO3 nanoparticles according to claim 1, characterized in that: The crystal form regulator is at least two of the Span-80, the glucose, the polyethyleneimine and the L-alanine; Preferably, the crystal form regulator is a compound of the polyethyleneimine and the L-alanine in a mass ratio of (1-2):1; or, the crystal form regulator is a compound of the polyethyleneimine and the Span-80 in a mass ratio of 1:(80-120); Preferably, the amount of the first crystal form regulator added in step (1) is 9% to 12% of the weight of Na2CO3 in the Na2CO3 aqueous solution; Preferably, the amount of the second crystal form regulator added in step (2) is 12% to 15% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution.

3. The method for preparing CaCO3 nanoparticles according to claim 1 or 2, characterized in that: The concentration of Na2CO3 in the Na2CO3 microemulsion is 0.25-1.2 mol / L, and the concentration of Ca(OH)2 in the Ca(OH)2 microemulsion is 0.25-1.2 mol / L.

4. The method for preparing CaCO3 nanoparticles according to any one of claims 1 to 3, characterized in that: The first surfactant and the second surfactant are independently selected from cetyltrimethylammonium bromide and / or Span-80; Preferably, the first co-surfactant and the second co-surfactant are independently selected from n-butanol and / or n-pentanol; Preferably, the first organic solvent and the second organic solvent are independently selected from cyclohexane and / or isooctane.

5. The method for preparing CaCO3 nanoparticles according to any one of claims 1 to 3, characterized in that: The amount of the first surfactant added in the step (1) is 2% to 5% of the weight of Na2CO3 in the Na2CO3 aqueous solution; Preferably, the first cosurfactant is added in an amount of 7% to 10% of the weight of Na2CO3 in the Na2CO3 aqueous solution; Preferably, the amount of the first organic solvent added is 35% to 38% of the weight of Na2CO3 in the Na2CO3 aqueous solution.

6. The method for preparing CaCO3 nanoparticles according to any one of claims 1 to 3, characterized in that: The amount of the second surfactant added in step (2) is 6% to 8% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution; Preferably, the amount of the second co-surfactant added is 10% to 12% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution; Preferably, the amount of the second organic solvent added is 50% to 55% of the weight of Ca(OH)2 in the Ca(OH)2 aqueous solution.

7. The method for preparing CaCO3 nanoparticles according to any one of claims 1 to 3, characterized in that: In the step (3), the molar ratio of Ca(OH)2 in the Ca(OH)2 microemulsion and Na2CO3 in the Na2CO3 microemulsion is (0.5-2):

1.

8. The method for preparing CaCO3 nanoparticles according to any one of claims 1 to 3, characterized in that: In the step (3), the Ca(OH)2 microemulsion is added to the Na2CO3 microemulsion by a peristaltic pump; Preferably, the rotation speed of the peristaltic pump is 50-100 rpm; Preferably, the stirring time is 1 to 3 hours; Preferably, the aging time is 10 to 15 hours.

9. The method for preparing CaCO3 nanoparticles according to any one of claims 1 to 3, characterized in that: In the step (4), the washing detergent is water and / or anhydrous ethanol; Preferably, the drying time is 10 to 15 hours; Preferably, the drying temperature is 60-100°C.

10. A CaCO3 nanoparticle, characterized in that: The CaCO3 nanoparticles are prepared by the preparation method described in any one of claims 1 to 9, and the average particle size of the CaCO3 nanoparticles is in the range of 29nm to 904nm, and the structure of the CaCO3 nanoparticles is a cubic structure, a hollow long rod structure, a blocky cubic structure, a regular tetrahedron structure, a hollow cubic structure or a lamellar cubic structure.